Application of an efficient exponential wide band model for the natural gas combustion simulation in a 300 kW BERL burner furnace. (5th February 2016) - Yan, Linbo; Yue, Guangxi; He, Boshu
Highlights: Natural gas combustion in a 300 kW BERL furnace is simulated and analyzed. Counter flow due to swirl velocity will be generated and is beneficial to stable combustion. Calculation results of simulations with the E-EWB and the WSGG models are compared. The simulation results with the E-EWB model are closer to the measured data. The simulation speed with E-EWB model is about 1.8 times slower than that with WSGG model. Graphical Abstract: Abstract: Methane is one of the most important radiation participating medium. However, the weighted-sum-of-gray-gas (WSGG) model which is widely used in the recent commercial computational fluid dynamics (CFD) software cannot address the contribution of methane to the effective absorption coefficient (EAC) when simulating the natural gas combustion. In this work, an efficient exponential wide band (E-EWB) model which accounts for the effects of many species including H2 O, CO2, CO and CH4 on EAC is proposed and numerical simulations are carried out for the natural gas combustion in a 300 kW BERL (Burner Engineering Research Laboratory) burner. The results including the distributions of axial velocity, gas temperature and the O2 mass fraction in the furnace obtained by the simulations with both the WSGG model and the E-EWB model are then analyzed and validated against the experimental data. The calculation efficiencies of the two simulations with the WSGG and E-EWB models are also compared. It is found that simulation with the E-EWB model generates much better results, although its calculation speed is about 1.8 times slower than that of the simulation with the WSGG model.